The human use of animals case studies in ethical choice - Orlans, F. Barbara (New York Oxford University Press, 1998)
"The first set of case studies on animal use, this volume offers a thorough, up-to-date exploration of the moral issues related to animal welfare. Its main purpose is to examine how far it is ethically justifiable to harm animals in order to benefit mankind. An excellent introduction provides a framework for the cases and sets the background of philosophical and moral concepts underlying the subject." "The Human Use of Animals will be welcomed by students and faculty in law, philosophy, ethics, public policy, religion, medicine, and veterinary medicine. It will also interest activists in the animal protection movement and members of animal protection organizations and Institutional Animal Care and Use Committees."--BOOK JACKET.
I. Introduction -- 1. Moral Issues about Animals -- II. Biomedical Research -- 2. Baboon-Human Liver Transplants: The Pittsburgh Case -- 3. Head Injury Experiments on Primates at the University of Pennsylvania -- 4. Patenting Animals: The Harvard "Oncomouse" -- 5. What Does the Public Have a Right to Know? -- III. Cosmetic Safety Testing -- 6. Beauty Without the Beast -- IV. Behavioral Research -- 7. Apes and Language: Washoe and Her Successors -- 8. Can Animal Aggression Be Studied in an Ethical Manner? -- 9. Monkeys Without Mothers -- V. Wildlife Research -- 10. The Death of a Vagrant Bird -- VI. Education -- 11. Dissection of Frogs: The Jenifer Graham Case -- VII. Food and Farming -- 12. Force-Feeding of Geese -- 13. Veal Crates and Human Palates -- 14. Fowl Deeds -- VIII. Companion Animals -- 15. Should the Tail Wag the Dog? -- 16. Where Should Research Scientists Get Their Dogs? -- IX. Religious Rites -- 17. Animal Sacrifice as Religious Ritual: The Santeria Case.
Includes bibliographical references and index.
Keywords: Animal experimentation -- Moral and ethical aspects -- Case studies; Animal welfare -- Moral and ethical aspects -- Case studies; Animal Welfare; Animal Use Alternatives; Animals, Laboratory